(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study conducted on a sample of 90 individuals from private universities in Baghdad, Iraq, shows that these universities possess a high level of strategic flexibility. This is reflected in their ability to adapt to environmental changes and competition in the educational sector. Innovation in academic programs and services is considered a key element that enhances the competitiveness of these universities. The study also demonstrates a clear positive impact of strategic flexibility on organizational culture. The results indicate that competitive flexibility plays a major role in strengthening organizational culture, while resource flexibility shows an important but less powerful effect. This underscores the importance of focusing on both aspects to improve the work environment in universities. The recommendations emphasize the need for private universities to develop programs that foster creative thinking and innovation. This can be achieved by establishing research and development centers that adopt and implement new ideas in line with market demands and student needs. Additionally, it is advised to implement comprehensive policies that focus on enhancing strategic flexibility in various aspects of university operations, whether in competitiveness or resource management. This will enable universities to adapt to future changes and achieve their goals effectively. Overall, the study highlights the significance of strategic flexibility as a fundamental factor in enhancing organizational culture in Iraqi private universities, necessitating the development of strategies that support continuous innovation and adaptation.